2021
DOI: 10.1108/compel-03-2021-0106
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of electromagnetic torque for induction motors with a novel non-skewed rotor structure

Abstract: Purpose Pulsating torques cause a number of problems in electrical machines, including mechanical vibrations, acoustic noise and the depreciation of mechanical equipment. In induction motors, the slot skewing method is an effective way to solve these issues; however, it has some drawbacks such as output torque drop, stray loss intensification due to inter-bar currents and iron loss increment. Besides, slot skewing may not be practical in higher-rated induction motors. In this regard, this paper introduces a mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 27 publications
(44 reference statements)
0
0
0
Order By: Relevance
“…The proposed skew method Improved air gap permeance modelling exhibits the desired torque ripple reduction (Kawase et al, 2009). As rotor skew increases, the length and the resistance of the rotor bars increase, which reduces the average torque at the rated slip to a minor extent as observed (Darjazini et al, 2021;Asad et al, 2021). In contrast, Kawase et al (2009) observed an optimum of the average torque for a skew of one rotor slot pitch.…”
Section: Implementation In Magnetic Equivalent Circuitsmentioning
confidence: 87%
“…The proposed skew method Improved air gap permeance modelling exhibits the desired torque ripple reduction (Kawase et al, 2009). As rotor skew increases, the length and the resistance of the rotor bars increase, which reduces the average torque at the rated slip to a minor extent as observed (Darjazini et al, 2021;Asad et al, 2021). In contrast, Kawase et al (2009) observed an optimum of the average torque for a skew of one rotor slot pitch.…”
Section: Implementation In Magnetic Equivalent Circuitsmentioning
confidence: 87%
“…Regarding the optimal selection of stator slot rotor bar (SSRB) combination, various articles for other industry applications can be found. The investigations have covered different combinations of SSRB from the point of view of noise [23], vibration, crawling, steady-state performance [24,25], rotor bar current waveform [26], etc.…”
Section: Methodsmentioning
confidence: 99%